DETERMINASI FISCAL STRESS PADA KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Ilham Sanjaya; Rita Martini; Muhammad Fauzan Ahnaf; Anton Trianto (Politeknik Negeri Sriwijaya, 2021)
This study aims to determine the effect of the growth of local revenue (PAD), capital expenditure growth, and economic growth on fiscal stress. Fifteen district/city governments in South Sumatra were sampled by purposive sampling. Secondary data is in the form of Realization Reports of Regional Revenue and Expenditure Budgets and data in the form of Domestic and Gross Regional Product data. The test results in capital expenditure growth affecting fiscal stress, while PAD growth and economic growth have no impact on budgetary pressure.